2018
DOI: 10.1177/2055668318777984
|View full text |Cite
|
Sign up to set email alerts
|

Development of the circumduction metric for identification of cervical motion impairment

Abstract: Introduction Chronic neck pain results in considerable personal, clinical, and societal burden. It consistently ranks among the top three pain-related reasons for seeking healthcare. Despite its prevalence, neck pain is difficult to both assess and treat. Quantitative approaches are required since diagnostic imaging techniques rarely provide information on movement-related neck pain, and most common clinical assessment tools are limited to single plane motion measurement. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Only three studies provided a sample size calculation [57,59,75]. Two studies gave no description of the definition for the control group [71,83]. Eleven studies had missing information on the reliability of outcome measurements [57, 58, 61, 63, 67, 72-74, 77, 82, 83].…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Only three studies provided a sample size calculation [57,59,75]. Two studies gave no description of the definition for the control group [71,83]. Eleven studies had missing information on the reliability of outcome measurements [57, 58, 61, 63, 67, 72-74, 77, 82, 83].…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…All 27 included studies were cross-sectional studies, with sample sizes ranging from 20 to 167. Nine studies reported on INP exclusively [58,59,63,66,67,71,72,78,79], eight studies on WAD only [57, 61, 64, 68-70, 77, 80], six studies assessed outcomes for WAD and INP separately [60,62,65,75,76,81], while another four studies reported on unclassified NP [73,74,82,83]. Eight studies, that included patients after WAD [60,69,70,[73][74][75][76][77] did not report on a specific grade according to the Quebec Task classification [84], while another eight studies included patients after WAD grade I [61,62,64,65,68,81], grade II [57,61,62,64,65,68,80,81], or grade III [57,61].…”
Section: Publications and Participantsmentioning
confidence: 99%
“…For instance, inertial motion units (IMUs) are small, cheap, accurate, reliable, and easy to apply in clinical practice [ 35 ]. These sensors have been validated for cervical, lumbar and hip analyses [ 36 , 37 ] and have been able to differentiate the lumbo-pelvic kinematics between healthy and back pain populations [ 3 ], and to classify subtypes of traumatic injuries in the cervical spine [ 38 ]. However, few studies have focused on the relationship between the kinematics of the neck or lower back with clinical scales [ 39 ], and most of them have focused only on chronic spinal pain populations [ 33 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various noninvasive three-dimensional motion capture systems are used in the field of cervical research in order to evaluate kinematic variables going beyond simple range of motion such as speed, acceleration and deceleration using electrogoniometers [16], ultrasound waves [17], optical-based systems [18,19] and inertial sensors [20] and so on. Nevertheless, their dimension, complexity, and cost make such systems often difficult to use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%